Pengaruh Media Pembelajaran Berbasis Ict (Information And Communication Technology) terhadap Kemampuan Menyimak Pidato Siswa Kelas X SMA Swasta Free Methodist 2 Medan - Herdika Jaya Harefa; Sarma Panggabean; Pontas. J. Sitorus (Journal of Language Education (JoLE), 2023)
This research aims to determine the effect of using ICT (Information and Communication Technology)-based learning media on the ability to listen to speeches of students at X Private Free Methodist High School 2 Medan for the 2023/2024 academic year. The sample for this research was 2 classes with 30 people per class who were randomly selected as the control class and the experimental class, namely the X-MIA experimental class and the X-IIS control class. This research instrument is a test in the form of essay questions. The assignment carried out was by giving post-test questions to the experimental and control classes. The data analysis technique used is the normality test using the F test, homogeneity test and hypothesis testing using the t test. Keywords: ICT (Information and Communication Technology) Based Learning Media, Listening to Speeches Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media pembelajaran berbasis ICT (Information and Communication Technology) terhadap kemampuan menyimak pidato siswa X SMA Swasta Free Methodist 2 Medan Tahun ajaran 2023/2024. Sampel penelitian ini yakni 2 kelas sebanyak 30 orang per kelas yang dipilih secara acak sebagai kelas kontrol dan kelas eksperimen, yaitu kelas eksperimen X- MIA dan kelas kontrol X- IIS. Instrumen penelitian ini bersifat uji tes yang berbentuk soal essay. Penugasan yang dilakukan ialah dengan memberikan soal post-test pada kelas eksperimen dan kontrol. Teknik analisis data yang digunakan yaitu uji normalitas menggunakan uji F, uji homogenitas dan uji hipotesis menggunakan uji t. Kata Kunci: Media Pembelajaran Berbasis ICT (Information and Communication Technology), Menyimak Pidato